Ազատազրկվածների ընտրելու իրավունքի հիմնախնդիրները ՀՀ-ում և եվրոպական երկրներում - Ս. Ա. Գինոսյան (ՀՀ ԳԱԱ հրատ.)
Изучение различных законодательных подходов стран Европейской конвенции о защите прав человека и основных свобод, а также соответствующих решений Европейского суда по правам человека приводит к заключению, что в некоторых странах активное избирательное право не является абсолютным и одинаковым для граждан, лишенных свободы. The suffrage is one of the basic rights of the citizen, giving him the opportunity to participate in governing of a state directly or through elected representatives. Having familiarized with various legislative approaches of the member states of the European Convention on Human Rights and Fundamental Freedoms, as well as analyzing the relevant decisions of the European Court of Human Rights, it can be noted that in some countries, active suffrage is not an absolute right and is not the same for citizens deprived of their liberty.
Keywords: Law